REMEDIASI MISKONSEPSI MENGGUNAKAN MODEL POE BERBANTUAN MEDIA KOMIK PADA MATERI GERAK LURUS DI SMP DARUT TAUHID SUNGAI RAYA - Purwasih Purwasih; Edy Tandililing; Diah Mahmuda (Universitas Tanjungpura, 2020)
AbstractThe aims of this research to determine the effectiviness of Predic-Observe-Explain Model using Comic to reduce students misconception in linear motion. This study was a quasy experimental with Pre-test Post-test Control Group Design. The population of this study was tenth grade students in SMP Darut Tauhid Sungai Raya. Theparticipants of this study were 28 students from VII A (control group) and 31 stundents from VII B (experiment group). Z test was used on this study with the significance is 5%. There was sifnificant diferences between Predic-Observe-Explain Model using Comic with conventional model to reduce student misconception in fluida statis. The effectiveness of the misconception remediation activities in linear motion is a accompanied by an Predic-Observe-Explain Model using Comic to reduce the number of students who experienced misconceptions using the DQM price of 70,7% (high category). Predic-Observe-Explain Model using Comic effective to reduce students misconception in linear motion concept. Keywords: Comic, linear Motion, Misconception, POE, Remediation.